2015
DOI: 10.1103/physrevb.91.115129
|View full text |Cite
|
Sign up to set email alerts
|

Generating functional approach for spontaneous coherence in semiconductor electron-hole-photon systems

Abstract: Electrons, holes, and photons in semiconductors are interacting fermions and bosons. In this system, a variety of ordered coherent phases can be formed through the spontaneous phase symmetry breaking because of their interactions. The Bose-Einstein condensation (BEC) of excitons and polaritons is one of such coherent phases, which can potentially crossover into the Bardeen-CooperSchrieffer (BCS) type ordered phase at high densities under quasi-equilibrium conditions, known as the BCS-BEC crossover. In contrast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 146 publications
1
34
0
Order By: Relevance
“…In semiconductor materials (with no cavity), it is well known that e–h Coulomb interactions can cause significant enhancement of the PL intensity around the Fermi edge at low temperature, even for a plasma state 31 32 . As found in our previous studies on the carrier population and optical gain spectra 17 18 , this effect was shown to survive also in our case ( Fig. 4B ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In semiconductor materials (with no cavity), it is well known that e–h Coulomb interactions can cause significant enhancement of the PL intensity around the Fermi edge at low temperature, even for a plasma state 31 32 . As found in our previous studies on the carrier population and optical gain spectra 17 18 , this effect was shown to survive also in our case ( Fig. 4B ).…”
Section: Resultssupporting
confidence: 92%
“…One of the advantages of this approach is the applicability to high-density regimes because electrons and holes are explicitly treated with their Coulomb interactions, in contrast to the other approaches assuming excitons as bosonic particles such as dissipative Gross-Pitaevskii equations. By taking into account the pumping baths and the vacuum photon bath, a closed set of equations for the cavity photon field a 0 , the polarization function p k , and the number of electrons n e, k and holes n h, k can be derived 17 18 within the Hartree-Fock (HF) approximation for the steady state as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work we also consider the equilibrium situation only, as inspired by the recent experimental demonstration of a thermal equilibrium excitonpolariton BEC in a high-quality microcavity [29]. The extension of our work to include dissipations is possible, following the standard Keldysh technique [30][31][32].…”
mentioning
confidence: 99%